Dyeing of Cationized Cotton with Natural Colorant from Purple Corncob. Issue 5 (3rd September 2018) - Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Mongkholrattanasit, Rattanaphol
ABSTRACT: In this investigation, dyeing of cotton fabric with natural dye extracted from purple corncob was attempted by means of pretreatment with a cationic agent, 3-chloro-2-hydroxypropyltrimenthylammonium chloride (CHTAC). Maximum color yield results were achieved when the fabric was pretreated with CHTAC at a concentration of 125 g/L, followed by dyeing at 100°C for 30 min in a dye bath adjusted to pH 9. The influence of meta- and post-mordanting with AlK(SO4 )2, CuSO4, FeSO4, and gallnut was subsequently explored. Compared with the unmordanted sample, post-mordanting enhanced K/S values and slightly improved light fastness, but both meta- and post-mordanting caused a reduction in wash fastness from an excellent to a fair level, with the exception of CuSO4 . Meanwhile, mordanting with gallnut increased the acid and alkaline perspiration fastness from a poor and fair to a good level.